Decision to export among Ghanaian manufacturing firms: Does export destination influence the entry sunk cost? - Mulangu, Francis M.; Olarinde, Luke O. (International Food Policy Research Institute, 2016)
Two nonexclusive hypotheses have been put forward to explain why exporters enjoy higher productivity than do non-exporters: self-selection and learning-by-exporting. In the case of a small economy such as Ghana’s, we suspect that self-selection to export is less prevalent because of the high sunk cost of export market entry. While this sunk cost is considered high in the case of developing countries, its magnitude and persistence will vary by the export destination. The present paper evaluates how export destination influences export entry sunk cost. We use a dynamic probit model that corrects for the correlation between the error term and the lagged dependent variable and find African destinations to be associated with both lower and less persistent sunk costs of exporting relative to other export destinations.